Geo-Spatiality in Asian and Oceanic Literature and Culture Worlding Asia in the Anthropocene - Chou, Shiuhhuah Serena; Kim, Soyoung; Wilson, Rob Sean. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This collection opens the geospatiality of "Asia" into an environmental framework called "Oceania" and pushes this complex regional multiplicity towards modes of trans-local solidarity, planetary consciousness, multi-sited decentering, and world belonging. At the transdisciplinary core of this "worlding" process lies the multiple spatial and temporal dynamics of an environmental eco-poetics, articulated via thinking and creating both with and beyond the Pacific and Asia imaginary.
Part 1:Unearthing and Historicizing Regions -- Chapter 1: Geo-Political Fantasy: Continental Action Movies -- Chapter 2: Transpacific and Interracial World-Making in Eddie Huang's Fresh Off the Boat -- Chapter 3: The Place of Worlding: Subaltern Cosmopolitanism in Central Asia and Korea -- Chapter 4: Beyond Complicities: China as Eco-Peril and Worlding the Techno-Dystopian -- Chapter 5: Queering South Pacific into Ono Hai in Leche -- Chapter 6: My Beast, My Brother, and My Alpha Creation in Taiwanese Sci Fi -- Part 2: Activism, Vision, and Intervention -- Chapter 7: Violence, Magic, Certainty: Towards a Journalistic Worlding of the Middle East -- Chapter 8: Refugee Migration through the Division System: On the Ethics of Co-Presence in Krys Lee's How I Became a North Korean -- Chapter 9: The Crusades and a Marginal History of Islam: Tariq Ali's Activism and Alternative World in The Book of Saladin -- Chapter 10: Zeugmatic Formations: Balikbayan Boxes and the Filipino Diaspora Across Asia-Pacific Worlds -- Chapter 11: Call Me Ishimaru: Sailing Transpacific Worlds of Labor and Community from Japan to Brazil to the Americas -- Part 3: Planetary Creation: Critique and Cosmos -- Chapter 12: Friction or Flow? Ecological Transnationalism in Japanese Animation -- Chapter 13: Hurricanes and Kaiju: Climate Change and Toxicity Across the Pacific in Guillermo del Toro's Pacific Rim -- Chapter 14: Albatross Unbound: Worlding the Plastic Sea -- Chapter 15: Agrarianism, Disappointment, and the Mystery of Witnessing -- Chapter 16: Listening to Archipelagic Rains -- Chapter 17: Trans-indigenous Coalitions and Ecological Ties Across Oceania (poetry) -- Chapter 18: Epilogue; Reworlding Asia: Towards Alchemies of Planetary Regeneration.
Keywords: Oriental literature; Australasian literature; Ecocriticism; Ethnology-Asia.; Culture; Asia-History.; Asian Literature; Australasian Literature; Ecocriticism; Asian Culture; Asian History